Electrolyte Solvation Structure Design for Sodium Ion Batteries - Tian, Zhengnan; Zou, Yeguo; Liu, Gang; Wang, Yizhou; Yin, Jian; Ming, Jun; Alshareef, Husam N. (Advanced science, 2022)
Sodium ion batteries (SIBs) are considered the most promising battery technology in the post‐lithium era due to the abundant sodium reserves. In the past two decades, exploring new electrolytes for SIBs has generally relied on the “solid electrolyte interphase (SEI)” theory to optimize the electrolyte components. However, many observed phenomena cannot be fully explained by the SEI theory. Therefore, electrolyte solvation structure and electrode–electrolyte interface behavior have recently received tremendous research interest to explain the improved performance. Considering there is currently no review paper focusing on the solvation structure of electrolytes in SIBs, a systematic survey on SIBs is provided, in which the specific solvation structure design guidelines and their consequent impact on the electrochemical performance are elucidated. The key driving force of solvation structure formation, and the recent advances in adjusting SIB solvation structures are discussed in detail. It is believed that this review can provide new insights into the electrolyte optimization strategies of high‐performance SIBs and even other emerging battery systems. This review focuses on the solvation structure of electrolytes in sodium ion batteries, elucidating the specific solvation structure design guidelines and their consequent impact on the electrochemical performance. The key driving force of solvation structure formation, and the recent advances in adjusting sodium ion battery solvation structures are discussed in detail.